STRATEGI PELAYANAN TOUR LEADER DALAM MENINGKATKAN KUALITAS PELAYANAN TRAVEL PT. MEIDA WISATA TERHADAP CALON JEMAAH HAJI DI MAKASSAR TAHUN 2022 (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research focuses on the service strategy of PT. Meida Wisata’s tour leader travel for prospective hajj pilgrims in Makassar in 2022, which aims to find out the steps of a tour leader’s service strategy, namely, good and guaranteed service for prospective pilgrims in Makassar in 2022, among the discussions or sub-problems of this research are 1) what are the service strategy steps taken by a tour leader in improving the quality of PT. Meida Wisata’s travel services for prospective hajj pilgrims in Makassar in 2022. 2) what is the perception of prospective hajj pilgrims regarding the services provided by a tour leader at PT. Meida Wisata in Makassar 2022. This type of research is qualitative with a management research approach, namely to interpret the steps of the tour leader service strategy in its functions (planning, organizing, actuating, controlling) and based on the service theory of A. Parasuraman, Valarie A Zeithmal, and Leonard L Berry SERVQUAL ( Service Quality) to identify the service quality of the tour leader which can be seen by a tour leader as an internal consumer and also by prospective pilgrims as an external consumer in PT. Meida Wisata travel. The data source of research was conducted by in-depth interviews with all informants, namely the tour leader as a key informant and prospective hajj pilgrims as observer informants, then reference searches, observations, and documentation was carried out, and then carried out data processing and analysis techniques as well as data reduction, data presentation, and conclusion. The results of this study indicate the strategic steps of the tour leader Travel service PT. Meida Wisata starts by planning the tasks and roles for the entire team, namely, the health team and tour guides in guiding while in Indonesia and while in the holy Land of Mecca to all prospective pilgrims. In addition, the tour leader continues his steps with the team in preparing physically and mentally for prospective pilgrims, namely, in the form of deepening knowledge about the pilgrimage and health in a gathering meeting that has a ukhuwah foundation to strengthen the process of carrying out the pilgrimage in 2022.